Panda resonator structure to generate four-wave mixing by nonlinear effect - Arthi, V.; Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Yupapin, Preecha Promphan; Chakkravarthy, S. Praveen; Rajan, M.S. Mani (Elsevier, 2019)
Finite-difference time domain (FDTD) simulation has been used for modeling of nonlinear optical interaction in a modified microring resonator as Panda structure. By proposing the Panda structure which has been modeled using both silicon and material (Chi2) with nonlinear effect, generation of four-wave mixing is feasible. Due to the nonlinear interaction between the two input waves as pump and signal within the microring resonators the results show the generation of three picks including the pump, signal and converted wave. In the case, if the silicon has been utilized as the core waveguide, the resonance interferences occur, where the high Qfactor of the resonance frequencies was obtained as 3.87 × 103 in the drop port outputs. Compared to silicon material, the nonlinear material shows a better power transferring performances. In the results showing the four-wave mixing, the converted wave has a lower power than the signal and pump.